Gender income differences among general practitioners with compulsory services in early career stage in underdeveloped areas: evidence from a prospective cohort study in China - Haoqing Tang; Mingyue Li; Huixian Zheng; Xiaotian Zhang; Xiaoyun Liu (BMC, 2024)
Abstract Background Gender equality and the gender income gap in medicine are long-standing global problems. Although gender-related differences have been widely studied in developed countries, they remain unclear in underdeveloped regions. In 2010, China initiated a national compulsory service program (CSP) to train qualified general practitioners in rural and remote areas. This study aimed to evaluate gender income differences for early career CSP and non-CSP (NCSP) graduates in underdeveloped areas. Methods A cohort study was conducted with 3620 CSP and NCSP graduates from four medical universities in Central and Western China. Baseline surveys and six follow-up surveys were conducted between 2015 and 2022. Incomes, including monthly mean income and proportion of performance-based income, were measured as the key outcome variables. Multivariate linear regression models were used to identify the gender income gap. Results NCSP graduates had higher average monthly incomes than CSP graduates. In the seventh year after graduation, the average monthly income for NCSP graduates was 7859 CNY while was 5379 CNY for CSP graduates. After controlling for demographic characteristics, the gender monthly income gap for CSP graduates was expanded from the fourth year (3.0%) to the sixth year (5.9%) after graduation, and that for NCSP graduates was expanded from the fifth year (11.9%) to the seventh year (16.3%) after graduation. Regarding performance-based income, it was 58.9% for NCSP graduates and 45.8% for CSP graduates in the seventh year after graduation. After controlling for performance-based income proportion, the gender income gap was reduced from 5.9 to 4.0% in the sixth year after graduation for CSP graduates, and from 16.3 to 14.4% for NCSP graduates in the seventh year after graduation. Conclusion An extensive and ever-increasing gender income gap exists among young doctors in the early stages of their careers in underdeveloped areas of China. The high proportion of performance-based income among men is one of the main explanations for the observed difference. A more explicit compensation system must be established to enhance support for female health workers.